Lectotype designations of Cerambycidae (Coleoptera) described by E. F. Germar in 1824 and J. C. Klug in 1825 and a new synonymy - Monné, Marcela L.; Monné, Miguel A. (Zootaxa, 2015)
Lectotype designation are provided for five species described by Germar: Cerambyx (Lissonotus) gagatinus Germar, 1824, Callichroma rufiventre Germar, 1824, Cerambyx lyciformis Germar, 1824, Rhinotragus dorsiger Germar, 1824, Callidium (Clytus) bisignatus Germar, 1824 and seven described by Klug: Stenopterus crinitus Klug, 1825, Stenopterus hirtipes Klug, 1825, Molorchus scoparius Klug, 1825, Stenopterus albicans Klug, 1825, Cerambyx phtisicus Klug, 1825, Cerambyx perforatus Klug, 1825 and Cerambyx tabidus Klug, 1825. New synonymy proposed: Cerambyx (Lissonotus) gagatinus Germar, 1824 (presently in the genus Rachidion, Cerambycinae, Trachyderini) = Prionus ornatus Dalman, 1823 (presently in the genus Poekilosoma, Prioninae, Anacolini).